Pengembangan olah pangan berbahan baku jagung dan talas bagi kelompok tani desa sungai enau kecamatan kuala mandor - Desdy Hendra Gunawan; Ridwan Salim (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
Taro and maize are agricultural products that have nutrients, especially fiber, so it is very good to be developed and its presence in the location of the activity is relatively abundant, so that further management is needed. The main objective of the community service activity is to provide guidance for the farmer group in the enau river village in downstreaming the locally owned raw materials in the form of taro and corn into processed products that have high sales value. The achievement is carried out with the theoretical and practical method of transferring appropriate technology accompanied by experts in their fields in the hope of ease of absorption and targeted plans. For convenience in implementing partners, it is divided into several small groups and is responsible for the products proclaimed. The results obtained in the form of 6 products consisting of flour, chips, taro cookies are preferred by all respondents, while cake is only 75%, while products made from corn which include nuggets and 100% corn donuts are preferred. The product is equipped with packaging that is labeled on each product